2001
DOI: 10.1111/1475-4754.00019
|View full text |Cite
|
Sign up to set email alerts
|

Strength, Toughness and Thermal Shock Resistance of Ancient Ceramics, and Their Influence On Technological Choice

Abstract: The basic underlying theory for the strength, toughness and thermal shock resistance of brittle multiphase clay ceramics, together with the measurement procedures to determine these parameters, are ®rst outlined. Published experimental data obtained for test bars containing different types of temper and ®red to a range of temperatures are then compared both with theoretical predictions and between themselves. The results con®rm that to produce pottery with high strength requires high ®ring temperatures and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
0
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(129 citation statements)
references
References 22 publications
4
119
0
6
Order By: Relevance
“…Mean porosity of the studied potsherds was 23% and they contained a predominance of 469 micro-and mesopores, which would aid the protection of adsorbed lipids during burial. The 470 porosity measurements also indicated that pottery production technology at Bylany was well-471 developed, which would have influenced the ways vessels were used and the extent to which 472 they survived in the archaeological record (Tite et al, 2001). The slightly acid pH burial 473 conditions at the site appear favourable for lipid preservation (e.g.…”
Section: Stable Carbon Isotope Analysis Of Lipid Residues and Animal mentioning
confidence: 99%
“…Mean porosity of the studied potsherds was 23% and they contained a predominance of 469 micro-and mesopores, which would aid the protection of adsorbed lipids during burial. The 470 porosity measurements also indicated that pottery production technology at Bylany was well-471 developed, which would have influenced the ways vessels were used and the extent to which 472 they survived in the archaeological record (Tite et al, 2001). The slightly acid pH burial 473 conditions at the site appear favourable for lipid preservation (e.g.…”
Section: Stable Carbon Isotope Analysis Of Lipid Residues and Animal mentioning
confidence: 99%
“…Medium synterization grade and non-calcareous coarse temper represented good technological choices to enhance the thermal shock resistance of the pots and to avoid lime spalling [31,32].…”
Section: Technological Aspectsmentioning
confidence: 99%
“…This vegetal temper was burnt out during many firing cycles and left elongated relict voids. Such secondary porosity generated during the firing/use of the bricks in the kilns, as well as that induced by coarse NPIs from the use of non elutriated clay, enhanced the thermal insulation of the kiln (Hein and Kilikoglou, 2007;Hein et al, 2008;Tite et al, 2001). Since very few samples of brick show very high sintering (i.e.…”
Section: Raw Materials: Processingmentioning
confidence: 99%